Validity and performance of cognitive scales in elderly patients with depression in a tertiary care hospital in Chennai - Malini, S.; Jayakrishnaveni, C.; Palaniappan, Saravanakumar (International Journal of Advances in Medicine, 2023)
Background: Late-life depression in older adults can cause reversible cognitive impairment, often resulting in pseudo-dementia. Cognitive impairment can lead to executive dysfunction, reduced flexibility, and difficulty thinking and decision-making. This study aimed to assess the validity and performance of cognitive scales in late-life depression among patients attending the outpatient department of the institute of mental health, Chennai. Methods: This prospective study included 360 patients aged >50 years who were diagnosed with depression and attended the OPD at the institute of mental health, Chennai. Baseline assessments were performed at the time of recruitment into the study (visit 1), and scheduled visits were performed every six months for two years (visits 2 to 5). Unscheduled visits were done every month, and adverse events were monitored and recorded periodically Results: Among 59 patients, 53.1% were female, 32.2% were diabetic, and 93.9% were experiencing subjective working difficulties. The Montreal cognitive assessment scale classified 51.4% as moderate, while the ADAS-cog and ACE scales classified 86% and 99.7%, respectively, as having abnormal mental status. However, a significant correlation and discrepancy between scores were observed for scales such as ACE, ADAS-cog, standardised mini-mental status examination, and Montreal cognitive assessment scale. A strong correlation was found between ACE, MMSE, MoCA, and ACE; however, FAST showed a significant negative correlation. The MoCA was strongly correlated with the MMSE, ACE, ADAS-cog, and Mini-Cog, indicating good alignment with the FAST. Conclusions: Cognitive scales strongly correlate with late-life depression in patients, suggesting an improvement in assessment, evaluation, and treatment to address cognitive deficits.